AN ENVIRONMENTAL AIR POLLUTION MONITORING AND ALERTING SYSTEM BASED ON SENSOR ARRAY AND RENEWABLE POWER SOURCE - Akanksha Shukla; Indra Thannaya (International Journal of Innovations in Engineering Research and Technology, 2021)
Air pollution has significant effect on the concentration of constituents in the atmosphere leading to effects like global warming and acid rains. To avoid such things an air pollution monitoring system is very important. The aim of the this paper is design and development of air pollution monitoring and alerting system based on wireless sensor network and comparison of the data based on real time acquisition and communication of air pollutants such as SO2, NO2, CO2, CO etc. System integrates a Development board(Ardunio), Air pollution sensors array (NO2, SO2, CO2 Sensors), Global positioning system Module (GPS-module) for location management, General packet radio services Module (GPRS-module) for data transmission with low power consumption,